Brain Derived Neurotrophic Factor (BDNF) Delays Onset of Pathogenesis in Transgenic Mouse Model of Spinocerebellar Ataxia Type 1 (SCA1) - Mellesmoen, Aaron; Sheeler, Carrie; Ferro, Austin; Rainwater, Orion; Cvetanovic, Marija (Frontiers in Cellular Neuroscience, 2019)
Spinocerebellar ataxia type 1 (SCA1) is a fatal neurodegenerative disease caused by an abnormal expansion of CAG repeats in the Ataxin-1 (ATXN1) gene and characterized by motor deficits and cerebellar neurodegeneration. Even though mutant ATXN1 is expressed from an early age, disease onset usually occurs in patient’s mid-thirties, indicating the presence of compensatory factors that limit the toxic effects of mutant ATXN1 early in disease. Brain derived neurotrophic factor (BDNF) is a growth factor known to be important for the survival and function of cerebellar neurons. Using gene expression analysis, we observed altered BDNF expression in the cerebella of Purkinje neuron specific transgenic mouse model of SCA1, ATXN1[82Q] mice, with increased expression during the early stage and decreased expression in the late stage of disease. We therefore investigated the potentially protective role of BDNF in early stage SCA1 through intraventricular delivery of BDNF via ALZET osmotic pumps. Extrinsic BDNF delivery delayed onset of motor deficits and Purkinje neuron pathology in ATXN1[82Q] mice supporting its use as a novel therapeutic for SCA1.